Nowcasting indicators of poverty risk in the European Union: A microsimulation approach - Jekaterina Navicke; Olga Rastrigina; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2013)
The at-risk-of-poverty rate is one of the three indicators used for monitoring progress towards the Europe 2020 poverty and social exclusion reduction target. Timeliness of this indicator is critical for monitoring the effectiveness of policies. However, due to complicated nature of the European Union Statistics on Income and Living Conditions (EU-SILC) poverty risk estimates are published with a 2 to 3 year delay. This paper presents a method that can be used to estimate (nowcast) the current at-risk-of-poverty rate for the European Union (EU) countries based on EU-SILC microdata from a previous period. The EU tax-benefit microsimulation model EUROMOD is used for this purpose in combination with up to date macro-level statistics. We validate the method by using EU-SILC data for 2007 incomes to estimate at-risk-of-poverty rates for 2008-2012, and where possible compare our predictions with actual EU-SILC and other external statistics. The method is tested on eight EU countries which are among those experiencing the most volatile economic conditions within the period: Estonia, Greece, Spain, Italy, Latvia, Lithuania, Portugal and Romania.
Keywords: C81; D31; I32; 330; microsimulation; poverty; Euromod; nowcast; income; European Union